Diagnostic and prognostic value of short-term metabolic response to human growth hormone in short stature - Clayton, Barbara E. (1971)
Metabolic tests of the response to three days of administration of human growth hormone (HGH) have been done on 55 patients aged 6·2 to 20·3 years. 22 had `isolated' growth hormone deficiency (or hyposomatotrophic short stature, HS), 16 CNS tumours or multiple hormone deficiencies, 6 short stature associated with low birthweight, 3 psychosocial short stature, 4 Turner's syndrome, 1 hereditary short stature, and 3 uncertain diagnosis. Height was measured at 3-monthly intervals for a full year, then HGH was given for a full year and the difference in rate, that is the acceleration during the growth hormone year, was calculated. The height measurements were all done by one measurer in 45 of the patients. In the metabolic test there were 5 baseline days followed by 3 days of a single injection of 10 IU HGH, then 2 final days. The means for urinary nitrogen excretion, blood urea, and urinary calcium excretion were calculated for the 5 baseline days and for the last 2 HGH days plus the one subsequent day. The difference between the means is given as a percentage of baseline values. The children with isolated growth hormone (GH) deficiency had a greater decrease in nitrogen excretion (33±3%) than the low birthweight cases and small children (7±5%), but there was overlap between individuals in the isolated deficiency group (range 12 to 66%) and the rest (range -12% to 42%); 2 deficient children were below a dividing line of 20%, and 1 Turner's syndrome and 3 psychosocial short stature children were above it. The tumour and multiple deficiency patients had an average fall of 40±3% and showed no overlap with the low birthweight group. Blood urea and calcium excretion gave a worse separation. Within the isolated deficiency and the tumour and multiple deficiency groups there was no relation between any metabolic parameter and the amount of growth acceleration in the first year of HGH treatment. In the HS, though not in the tumour patients, there was a correlation (-0·60) between the decrease in percentage nitrogen excretion and peak GH level on stimulation and between per cent decrease in urinary nitrogen excretion and per cent decrease in blood urea (0·76). We conclude that the differential diagnostic value of the short-term metabolic test is very limited now that we have tests of GH response; and that in cases of isolated GH or multiple pituitary hormone deficiency the result of the metabolic test does not predict at all the height acceleration obtained on HGH treatment.